Frekuensi Konsumsi Junk Food Dengan Kejadian Menarche Dini Pada Remaja Putri: Junk Food Consumption Frequency with Early Menarche Incidence in Young Women - Nurhayati, Risa; Purwandari, Henny (Jurnal Kebidanan Midwiferia, 2023)
Menarche as a sign of puberty. Menarche can occur early, one of which is due to nutritional status such as junk food and if consumed in excess will stimulate accelerated maturity of the reproductive organs. The purpose of this study was to determine the relationship between the frequency of junk food consumption and the incidence of early menarche in young women at SDN Ja'an III Kec. Gondang Kab. sleepy. The research design was cross sectional with 30 respondents taken by total sampling. The dependent variable is early menarche, the independent variable is consumption of junk food. These two variables were measured using a questionnaire about junk food and menarche data. After the data was obtained, the results were analyzed through Spearman rank with a significance of α 0.05. The results of the study were that most of the 21 respondents (70%) consumed junk food 1-2 times/week and almost all of them, namely 25 respondents (83%) who consumed, did not experience early menarche. Statistical test results using the Spearman rank test p value = 0.000. Means p value = 0.000 ≤ α (0.05) so that Ha is accepted that there is a relationship between the frequency of consumption of junk food and the incidence of early menarche in young women. The correlation coefficient is 0.799 with a very strong relationship. Based on the results of the study, it was concluded that consumption of junk food continuously triggers excess nutrition. Excess nutrition will affect the development and maturity of the reproductive organs.